Impactos socioambientais causados pelos resíduos sólidos cemiteriais: um estudo multicasos em cemitérios públicos da região geográfica intermediária de Maceió-AL - Santos, Gabriela Moreira dos (2025)
Disorderly urban expansion, lack of adequate planning and the absence of modern infrastructure in public cemeteries contribute to a series of problems that affect both public health and the environment. These spaces have attracted attention due to their potential for environmental pollution and are seen as sources of contamination, and their activities are subject to environmental licensing, as provided for in the resolutions of the National Environmental Council. There is a possibility of soil degradation and water contamination by leachate and solid waste, which threaten human health and the environment and require solutions capable of reducing the impacts attributed to cemetery activities. This research aimed to describe the socio- environmental impacts of public cemeteries in cities in the state of Alagoas based on the analysis of solid waste generation and environmental disposal thereof. A qualitative methodological approach was adopted through the multi-case study strategy, limited to 12 (twelve) public cemeteries in the intermediate geographic region of Maceió-AL. The methodological procedures involved a systematic literature review on the issue, followed by observational research in public cemetery environments, where data were collected from non- participant observations and photographic records. As a result of the SLR, based on the extraction of data from 27 primary studies identified as relevant by the search string, the most mapped types of cemetery solid waste were construction waste and exhumation remains; the proposed interventions involved the development of management plans, environmental education, and maintenance and cleaning of the sites; in addition to the adoption of new cemetery practices. As a result of the observational research in the field, the lack of adequate infrastructure in the cemeteries was evidenced, aggravating the environmental problems with pollution by leachate and solid waste from exhumations without adequate disposal.